A simple wire design to protect the gums during inter-proximal stripping - K C Prabhat; Sandhya Maheshwari; Sanjeev Kumar Verma; Kusum Bharti (Wolters Kluwer Medknow Publications, 2013)
Introduction: Protection of gingiva during the inter-proximal reduction (IPR) is very essential and it is one of the most difficult tasks during IPR. Clinical Innovation: Present innovation discusses the chair-side construction of a simple wire design and its clinical use to prevent the gingival trauma during IPR. Discussion: During the IPR interproximal, gingiva should be protected by an indicator device. This wire design protects the gingiva from interproximal strips or burs during IPR. It has advantages of ease of use and can be sterilize for reuse.